2019
DOI: 10.1002/cctc.201901078
|View full text |Cite
|
Sign up to set email alerts
|

Insights on the One‐Pot Formation of 1,5‐Pentanediol from Furfural with Co−Al Spinel‐based Nanoparticles as an Alternative to Noble Metal Catalysts

Abstract: CoAl-spinel nanoparticles prepared by liquid-feed flame spray pyrolysis (LÀ F FSP) and activated by reduction at different temperatures were used to investigate the hydrogenation process of furfural (FA) under mild conditions. Reduction of the spinel at 500°C resulted in high FA conversion and selectivity to furfuryl alcohol (FFA, 81 % yield, in 1 hour). Reduction at higher temperatures (i. e., 700 and 850°C) led to the direct formation of diols (i. e., 1,5-PeD and 1,2-PeD) from FA. The differences in activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 29 publications
(48 reference statements)
1
22
0
Order By: Relevance
“…The remarkable stability of Co 2 -Ca 4 -Al 3 in long-term performance of the glycerol hydrogenolysis could be attributed to the outter layer CaCO 3 covering on surface of the catalyst, preventing the active species (Co, Ca, Al) from leaching and aggregation. Futhermore, the strong interaction between Co and Al species in the spinel may play an additional role in stabilizing Co 0 species, in line with a previous report …”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The remarkable stability of Co 2 -Ca 4 -Al 3 in long-term performance of the glycerol hydrogenolysis could be attributed to the outter layer CaCO 3 covering on surface of the catalyst, preventing the active species (Co, Ca, Al) from leaching and aggregation. Futhermore, the strong interaction between Co and Al species in the spinel may play an additional role in stabilizing Co 0 species, in line with a previous report …”
Section: Resultssupporting
confidence: 91%
“…Next, once the Co-based HT precursors were reduced, it can be seen from Figure that the characteristic lamellar structure of HT disappeared for all samples. For Co 6 -Al 3 (Figure a), six new diffraction peaks at 19.0°, 31.2°, 36.8°, 44.8°, 59.5°, and 65.1° (labeled as ω) can be observed obviously, which were ascribed to the diffraction of {1 1 1}, {2 2 0}, {3 1 1}, {4 0 0}, {5 1 1}, and {4 4 0} planes of CoAl 2 O 4 spinel (JCPDS 44-0160), respectively, reflecting the formation of the spinel structure with the good crystallinity. , Notably, either the Co 0 or CoO phase was not observed on the Co 6 -Al 3 catalyst, implying a high dispersion of Co species. Comparatively, after introducing Ca­(II) species into the catalysts, it was found that the crystallinity of CoAl 2 O 4 became poor as compared with that of Co 6 -Al 3 (Figure a–f), which could be attributed to the introduction of Ca­(II) into the crystal lattice of cobalt-based spinel. ,, As such, CaO-CoAl 2 O 4 mixed metal oxides were formed with an increasing dosage of Ca­(II), arising from incompatibility of the atomic radii of Al and Ca.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 The conversion of furfural to the diols involves multiple steps, including the first step of hydrogenation for the production of FA, 24 the second step for the opening of the furan ring in FA, 25 and the third step of the further hydrogenation of the reaction intermediates formed from the FA. 26,27 FA is an essential reaction intermediate for the production of diols, which can be further hydrogenated to THFA via hydrogenation of the furan ring 12,28 or can be converted to levulinic acid/esters via the aid of acid catalysts. 29,30 It has been reported that alkaline sites could aid the opening of the furan ring or the ring structure to form the unsaturated diols that could be further hydrogenated.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The conversion of furfural to the diols involves multiple steps, including the first step of hydrogenation for the production of FA, the second step for the opening of the furan ring in FA, and the third step of the further hydrogenation of the reaction intermediates formed from the FA. , FA is an essential reaction intermediate for the production of diols, which can be further hydrogenated to THFA via hydrogenation of the furan ring , or can be converted to levulinic acid/esters via the aid of acid catalysts. , It has been reported that alkaline sites could aid the opening of the furan ring or the ring structure to form the unsaturated diols that could be further hydrogenated. , Thus, the effective catalysts for the selective conversion of furfural to diols should first have the capability to hydrogenate the carbonyl functionality in furfural while avoids the hydrogenation of furan ring in FA to form THFA. Second, the acidic sites on the surface of the catalysts should be minimized to prevent the conversion of FA to levulinic acid/ester via the acid-catalyzed route.…”
Section: Introductionmentioning
confidence: 99%